2012
DOI: 10.1021/ma3019014
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinylphosphonate)s with Widely Tunable LCST: A Promising Alternative to Conventional Thermoresponsive Polymers

Abstract: Novel statistic copolymers of dialkyl vinylphosphonates have been synthesized via rare earth metal-mediated group transfer polymerization using easily accessible tris-(cyclopentadienyl)ytterbium. The copolymerization parameters have been determined by activity measurements showing the formation of almost perfectly random copolymers (r 1 , r 2 ∼ 1). Thus, the polymerization rate of vinylphosphonate GTP is mainly limited by the steric demand of growing polymer chain end. The obtained copolymers of diethyl vinylp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 63 publications
4
90
0
Order By: Relevance
“…Previous studies on DAVP‐polymers showed that statistical copolymers exhibit a tunable LCST between 5 and 92 °C. The cloud points correlate linear with the content of hydrophilic/hydrophobic comonomer . The same effect was shown in the block copolymers; the introduction of small amounts of dimethylvinylphosphonate (DMVP) or di‐ iso ‐propylvinylphosphonate (DPVP), statistically incorporated into the DEVP block, shifted the cloud points.…”
Section: Functional (Co)polymerssupporting
confidence: 53%
See 1 more Smart Citation
“…Previous studies on DAVP‐polymers showed that statistical copolymers exhibit a tunable LCST between 5 and 92 °C. The cloud points correlate linear with the content of hydrophilic/hydrophobic comonomer . The same effect was shown in the block copolymers; the introduction of small amounts of dimethylvinylphosphonate (DMVP) or di‐ iso ‐propylvinylphosphonate (DPVP), statistically incorporated into the DEVP block, shifted the cloud points.…”
Section: Functional (Co)polymerssupporting
confidence: 53%
“…Random copolymers are prepared by pre‐addition mixing of monomers of the same kind (methyacrylates, acrylates, DAVP, etc.) and subsequent addition to the catalyst …”
Section: Functional (Co)polymersmentioning
confidence: 99%
“…However, REM‐GTP offers access to strictly linear polymer growth and very narrow molecular‐weight distributions ( Đ <1.1), and is applicable to a vast feedstock of monomers. In particular, dialkylvinyl phosphonates (DAVPs), which exhibit tunable thermoresponsive behavior, offer an alternative to the established polymers . Our group has made great progress in developing highly active catalysts for REM‐GTP and elucidating their mechanism of action .…”
Section: Introductionmentioning
confidence: 99%
“…For determination of LCST, a concentration of 0.2 wt% was used and measurements were performed at a fixed wavelength (600 nm), which is far from azobenzene absorption. LCST was defined as the temperature corresponding to 10% decrease in the optical transmittance based on literature reports . Precursor polymers N 3 ‐Azo‐PNIPAM 48 and N 3 ‐Azo‐PNIPAM 79 exhibited a sharp decrease in transmittance with an increase in temperature and the LCST was determined to be 28 and 32 °C, respectively.…”
Section: Resultsmentioning
confidence: 99%